Pathogenetic mechanisms of Valsalva retinopathy development - L. D. Pushkaryova; I. V. Zapuskalov (Бюллетень сибирской медицины)
The purpose of this review was to analyze existing data in the literature research on some pathogenetic mechanisms of the Valsalva retinopathy development. The main causes of retinal vessel damage of vascular are described. They include arterial pressure and central venous pressure elevation. The latter is transmitted to retinal veins and may cause retinal capillar wall ruptur.